Strategic thinking in the shadow of self-enhancement: Benefits and costs - Grüning, David; Krueger, Joachim I. (The British journal of social psychology, 2024)
Using a variant of the hide-and-seek game, we show in three studies that self-enhancement can help or hinder strategic thinking. In this guessing game, one player chooses a number while another player tries to guess it. Each player does this either in a random fashion (throwing a mental die) or by active thinking. The structure of the game implies that guessers benefit from thinking about a number, whereas choosers are disadvantaged. Yet, regardless of their role, respondents prefer to actively think about a number. For choosers, the belief they can outthink the opponent amounts to self-enhancement, whereas for guessers, the same belief can be rationally justified. We discuss the implications of the findings for theories of strategic cognition and applications to real-world contexts.
Gesehen am 09.09.2024